5′-Hydroxy-5′-homoaristeromycin: Synthesis and antiviral properties. Issue 9 (15th May 2018) - Chen, Qi; Liu, Chong; Bowlin, Terry L.; Schneller, Stewart W.
Graphical abstract: Abstract: Synthetically combining the C-4′ side-chain structural features of the antiviral candidates 5′-methylaristeromycin and 5′-homoaristeromycin into a diastereomeric pair of C-4′ side-chain dihydroxylated aristeromycins (6 and 7 ) is reported. Broad antiviral analyses of the both targets found promising effects towards HBV (6, 6.7 μM and 7, 7.74 μM) and HCMV (only 7, 0.72 μM). No other activity was found. Neither of the diastereomers was cytotoxic in the assays performed.